Epidemiology of Buruli Ulcer in Victoria, Australia, 2017–2022 - Bhavi Ravindran; Daneeta Hennessy; Miriam O’Hara; Ee Laine Tay; Rosalina Sa’aga Banuve; Jodie McVernon; Kylie Carville (Emerging Infectious Diseases)
Buruli ulcer (BU) is a rare, neglected tropical disease caused by Mycobacterium ulcerans that can lead to severe skin ulcers. To determine the epidemiology of BU in Victoria, Australia, during 2017–2022 we analyzed surveillance data. A total of 1,751 cases of BU were notified; 968 (55%) patients were male and 781 (45%) female (2 were missing sex data), and 984 (56%) resided in established BU-endemic areas, although an increasing number were in new BU-endemic areas. Most cases (83%, 1,301) were classified as category I. Multivariate modeling demonstrated that factors for severe BU included being male, being older, and living in a new BU-endemic or non–BU-endemic area. A relatively shorter interval between first visit to a clinician and receipt of diagnosis was protective against severe disease. The expansion of BU-endemic areas throughout Victoria remains a public health concern and calls for targeted action, particularly for patients and clinicians in new BU-endemic areas.